The Effectiveness of the Project Based Learning (PjBL) Model with a Deep Learning Approach on the Critical Thinking Skills of Fifth Grade Students at SDN Pejaten 2 - Permatasari, Anita; Sopandi, Wahyu; Hendriawan, Deri; Pujiasih, Yunita (International Conference on Elementary Education, 2025)
Previous studies on Project-Based Learning (PjBL) have demonstrated its potential to enhance higher-order thinking skills; however, limited research has integrated PjBL with a Deep Learning approach at the elementary school level, particularly in the Indonesian context. This study offers a novel contribution by combining PjBL with structured deep-learning processes—conceptual elaboration, reflective inquiry, and metacognitive reinforcement—to strengthen students’ critical thinking development more comprehensively. This research employed a one-group pretest–posttest design involving 64 fifth-grade students at SDN Pejaten 2 during a four-meeting intervention. Critical thinking skills were measured using a validated essay test, and data were analyzed using a paired sample t-test and effect size calculation. Findings show a significant improvement in students’ critical thinking skills, with the mean score increasing from 63.1 (pretest) to 82.4 (posttest) (t = 6.32; p < 0.001). The intervention yielded a large effect size (Cohen’s d > 0.80), indicating strong practical significance. These results highlight that integrating PjBL with a Deep Learning approach produces deeper cognitive engagement compared with conventional PjBL implementations reported in prior literature. This study provides empirical evidence that project-based learning enriched with deep-thinking processes can serve as an effective pedagogical model for fostering 21st-century competencies in elementary education.